Sıçanlarda formaldehitin oluşturduğu toksik etkiye karşı melatonin’in koruyucu etkisinin incelenmesi - Aydemir, Sezgin (My University, 2017)
Amaç: Formaldehit (FA) genotoksik özelliği bilinen, IARC tarafından “Grup I, insanlar için karsinojen” olarak sınıflandırılan ve insanlar üzerinde sinir, solunum ve üreme sistemi gibi sistemler üzerine çeşitli toksik etkilere sahip bir kimyasaldır. Melatonin (MEL) epifiz bezi tarafından salgılanan bir nörohormon olup, temel fizyolojik fonksiyonu sirkadyen ritmi düzenlemektir. Bu çalışmada, sıçanlarda uygulaması ile FA-inh+MEL ve FA-ip+MEL gruplarında %DNAT düzeylerinde anlamlı bir düşüş olduğu görüldü (p<0,001). Aynı şekilde, benzer bulgular 8-OHdG düzeyleri sonuçlarından da elde edildi. Oksidatif stresin biyogöstergeleri olan MDA, MPO, NO, luminol ve lusigeninin FA-inh ve FA-ip gruplarında anlamlı şekilde arttığı, FA-inh+MEL ve FA-ip+MEL gruplarında ise azaldığı belirlendi. GSH'ın ise FA-inh ve FA-ip gruplarında anlamlı olarak azaldığı, FA-inh+MEL ve FA-ip+MEL gruplarında arttığı görüldü. Işık mikroskopu incelemelerinde dokularda histomorfolojik değişiklikler gözlendi ve bu etkilerin MEL ile azaldığı görüldü. Sonuçlar: MEL’in oksidan-antioksidan durumu dengeleyerek FA’nın indüklediği oksidatif doku ve DNA hasarına karşı koruyucu etkisinin olduğu düşünülmektedir.

Purpose: Formaldehyde (FA) is a chemical known to be genotoxic, classified as “carcinogenic to humans in Group 1” by IARC, and has various toxic effects on humans such as nervous, respiratory and reproductive systems. MEL is a neurohomone secreted by pineal gland and it regulates the circadian rhythm. In this study, it is aimed to investigate the potential protective effects of MEL on FA induced toxicity in rats. Materials and Methods: Wistar albino rats were included and randomly divided into 6 groups (n=8). Related groups was exposed to FA by inhalation (FA-inh; 6 ppm, 5 day/ week, 6 weeks) and intraperitoneally (FA-ip; 10 mg/ kg/ day, 14 days). MEL was injected at a dose of 10 mg/ kg/ day in related groups (FA-inh+MEL, FA-ip+MEL and MEL). The Comet assay and measurement of 8-hydroxyguanosine (8-OHdG) levels were conducted with blood samples. Determinations of MDA and GSH levels, MPO activities and chemiluminscence measurements were applied in the lung, liver and kidney tissues. Histopathological changes were investigated with the light microscope. Results: Increased DNA damage was observed in FA-inh and FA-ip groups in the comet assay (%DNAT). MEL treatment reduced statistically %DNAT levels in FA-inh+MEL and FA-ip+MEL groups (p<0,001). Similar findings were observed in the results of 8-OHdG levels. As biomarkers of oxidative stress, MDA, MPO, NO, luminol and lucigenin levels were increased in FA-inh and FA-ip groups, decreased in FA-inh+MEL and FA-ip+MEL groups. A significant decrease in GSH levels in FA-inh and FA-ip groups, while an increase in the FA-inh+MEL and FA-ip+MEL groups were observed. In the light microscopic investigations, histomorphological changes were observed and these effects reduced by MEL treatment. Conclusion: Results suggests that MEL may be beneficial against FA-induced oxidative tissue and DNA damages by balancing oxidant/ antioxidant status.
Keywords: chemiluminescence; comet assay; comet tekniği; Farmasötik toksikoloji; formaldehit; histopathology; histopatoloji formaldehyde; kemilüminesans; Melatonin; Sağlığa etkisi